OPTIMALISASI PEMANFAATAN PANGKALAN PENDARATAN IKAN (PPI) LAPPA KABUPATEN SINJAI PROVINSI SULAWESI SELATAN - Eka Nur Alam; Danial Danial; Syahrul Djafar (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2025)
In supporting the smooth running of the Lappa Fish Landing places activities, adequate support facilities are needed. The non-operationalization of one of the facilities will hamper the smooth running of the port activities. This problem is often found in many fishing ports. FLP Lappa is one of 23 FLP in South Sulawesi Province that can contribute to Regional Original Income. The purpose of this study is to analyze the facilities of the Lappa Fish Landing Places to optimize the facilities of the Lappa Fish Landing Places that have not been utilized. The research method is a survey method. in the form of direct observation carried out to obtain facts from existing symptoms and seek factual information in the Lappa Fish Landing Places area then conduct a descriptive analysis before identifying existing facilities and activities and recalculating the capacity of the fish auction place, dock and port pool. The results of the study show that based on the thirteen types of fishery port activities listed in No: PER.08/MEN/2012 concerning fishery ports, the problem at FLP Lappa is that there are still facilities and infrastructure that have not been optimally utilized.